2018
DOI: 10.1038/s41419-018-1059-y
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of HPGD by miR-146b-3p promotes cervical cancer cell proliferation, migration and anchorage-independent growth through activation of STAT3 and AKT pathways

Abstract: While the application of early screening and HPV vaccines has reduced the incidence and mortality rates of cervical cancer, it remains the third most common carcinoma and fourth leading cause of cancer-associated death among women worldwide. The precise mechanisms underlying progression of cervical cancer are not fully understood at present. Here, we detected significant down-regulation of 15-hydroxyprostaglandin dehydrogenase (HPGD) in cervical cancer tissues. Overexpression of HPGD inhibited cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…The activation of akt phosphorylation serves a role in promoting tumor cell proliferation, antiapoptosis and chemotherapy tolerance, and has been defined as an oncogene (17). The results of the present study demonstrated that activation of the Akt signaling pathway significantly promoted the proliferation and antiapoptotic effect in cervical cancer cells, which was consistent with earlier findings (13,18,19). Several studies have reported that TriM14, a core protein, regulates the biological behavior of tumors through various signaling pathways, such as the SPHK1/STaT3 and akt signaling pathways (20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 93%
“…The activation of akt phosphorylation serves a role in promoting tumor cell proliferation, antiapoptosis and chemotherapy tolerance, and has been defined as an oncogene (17). The results of the present study demonstrated that activation of the Akt signaling pathway significantly promoted the proliferation and antiapoptotic effect in cervical cancer cells, which was consistent with earlier findings (13,18,19). Several studies have reported that TriM14, a core protein, regulates the biological behavior of tumors through various signaling pathways, such as the SPHK1/STaT3 and akt signaling pathways (20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 93%
“…It participates in primordial follicle development and maintenance in mice [ 44 ], has higher expression levels in the follicular stage than the luteal stage in sheep experiments [ 45 ], or suppresses colorectal cancer cell viability and proliferation [ 46 ], but when downregulated, it enhances oocyte maturation and cell survival [ 47 ] or might serve as an ovarian cancer biomarker [ 39 , 48 ]. MiR–146 is reported to control reproductive functions by inhibiting the release of ovarian progesterone [ 49 ], whereas the downregulation of miR–146b–3p expression suppresses the proliferation and migration of cervical cancer cells [ 50 ]. Family members of miR–34 are involved in the development in both sexes of bovine gametes and embryos, but primary miR–34b/c is only detected in primordial oocytes and reproductive tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPGD (15-hydroxyprostaglandin dehydrogenase), which suppresses cell proliferation and migration, was identified as a direct target of miR-146b-3p in cervical cancer by miRNA microarray and bioinformatics analyses [81]. One group used miRNA microarray method and found that miR-188, miR-99, miR-125b were downregulated, while miR-223 was upregulated in cervical cancer.…”
Section: Systems Biology Approaches In Cervical Cancermentioning
confidence: 99%